The role of axin in the degradation of B-catenin in human oesophageal squamous cell carcinoma - Bezuidenhout, Belinda Catherine (My University, 2009)
Axin, in combination with adenomatous polyposis coli (APC), forms the scaffold of the β-catenin degradation-targeting complex. Intricate interactions within this complex lead to the phosphorylation and subsequent ubiquitination of β-catenin, followed by proteosome-mediated degradation. Low density lipoprotein receptorrelated protein 5 (LRP5), the canonical Wnt coreceptor, is able to function in axin inhibition, by recruiting it to the plasma membrane in response to canonical Wnt/β- catenin signalling. This study investigates the influences of each of these proteins within the context of human oesophageal squamous cell carcinoma (HOSCC). Western immunoblotting, and subsequent densitometric analysis of whole cell protein lysates revealed the presence of differing levels of β-catenin, axin and APC in five oesophageal carcinoma cell lines. Furthermore, both β-catenin and axin were able to associate with the plasma membrane, and, along with APC, were shown to localize to the nucleus. Immunofluorescence experiments confirmed this distribution pattern for β-catenin. APC and β-catenin were co-immunoprecipitated, displaying the interaction between components of the degradation-targeting complex. Relatively high levels of axin were detected at the plasma membrane, and so studies on LRP5 were commenced. LRP5 was detected in all five cell lines, and unexpectedly low levels of LRP5 at the plasma membrane were confirmed by indirect immunofluorescence. In response to EGF (10 ng/ml) treatment, there were a number of differences observed in the different cell lines, but average levels of LRP5 “peaked” at 3 hours. Further investigation revealed that each cell line had an almost unique response to EGF treatment when it came to axin plasma membrane-localization. These results confirm the influence of growth factors on HOSCC, as well as indicate that axin and its role in oesophageal tumourogenesis must, therefore, be influenced by additional intermediates not assayed in this study.